Ute’ Sainak: Relasi Babi dengan Orang Mentawai di Rereiket, Siberut Selatan - Ade Irwandi; Maskota Delfi; Yevita Nurti (Universitas Batanghari Jambi, 2022)
For the Mentawai people in Rereiket, pigs are very important animals. This is reflected in their social and cultural life through traditional ceremonies (punen). Pigs are used as an intermediary (gaud) in a traditional ceremony whose purposes are offerings, worship, symbols and requests for thanks and fortune-telling activities. This is motivated by the belief of the Rereiket People, namely Arat Sabulungan which regulates human relations with nature, fellow humans and other creatures (spirits). In addition, pigs also function as the most important property, because they can be used as dowry payments (alat toga), tulou (customary fines) and trade (economics) and otcai (gifts). The relationship that the Rereiket people build with pigs is a cultural ploy, where the insistence on modernization through development has obscured the culture of the Rereiket people. Thus, inside the Uma (traditional house) the skull of a pig's head is displayed and becomes a symbol that the ritual continues. The pig skull is called Ute 'Sainak which means that even in the urgency of modernization the cultural agenda (custom rituals) still takes place in the living spaces of the Rereiket people. So that Ute' Sainak became a strategy to maintain the life and cultural identity of the Mentawai people in Rereiket.